Case Report: Sebaceous lymphadenocarcinoma arising in parotid gland: eighth documented case with lymph node metastasis - Ru, Lu; An, Fengxian; Zou, Bo (Frontiers in Oncology, 2025)
BackgroundSebaceous lymphadenocarcinoma (SLAC) represents an extremely rare parotid malignancy, hypothesized to originate through malignant transformation of sebaceous lymphadenoma. To date, fewer than ten histopathologically confirmed cases have been documented globally.Case summaryA 33-year-old female presented with a persistent, painless left parotid mass that persisted despite anti-infective therapy. The patient underwent a comprehensive diagnostic workup prior to surgical resection. Histopathological examination of the specimen revealed sebaceous lymphadenoma with distinct foci of malignant transformation to SLAC, confirming a localized malignant process. Based on a review of the literature, this case represents the eighth reported instance of SLAC and the third with pathologically confirmed lymph node metastasis.ConclusionSLAC most commonly presents as a painless parotid mass. Surgical resection is the cornerstone of therapy, with individualized use of radiotherapy. While early outcomes may be favorable, long-term surveillance is essential. International collaboration is urgently needed to establish registries and define standardized management guidelines for this exceedingly rare malignancy.